2004
DOI: 10.1111/j.1067-1927.2004.012208.x
|View full text |Cite
|
Sign up to set email alerts
|

The fibroblast‐populated collagen matrix as a model of wound healing: a review of the evidence

Abstract: The fibroblast-populated collagen matrix (FPCM) has been utilized as an in vitro model of wound healing for more than 2 decades. It offers a reasonable approximation of the healing wound during the phases of established granulation tissue and early scar. The gross and microscopic morphology of the FPCM and the healing wound are similar at analogous phases. The processes of proliferation, survival/apoptosis, protein synthesis, and contraction act in similar directions in these two models, and the response to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 161 publications
7
130
0
13
Order By: Relevance
“…43 The reorganizing ECM has been shown to affect the wound contraction. 38 To further elucidate the functional role of FGFR1OP2/wit3.0, we have developed fibroblastic cells that were derived from mouse ES cells carrying Floating collagen gel contraction assay revealed that both oral and skin fibroblasts transduced by FGFR1OP2/wit3.0␤ lentiviral vectors (dotted lines) increased gel contraction rates. E: SNP1, SNP2, and SNP1/2 of FGFR1OP2/wit3.0␤ increased collagen gel contraction rates.…”
Section: Discussionmentioning
confidence: 99%
“…43 The reorganizing ECM has been shown to affect the wound contraction. 38 To further elucidate the functional role of FGFR1OP2/wit3.0, we have developed fibroblastic cells that were derived from mouse ES cells carrying Floating collagen gel contraction assay revealed that both oral and skin fibroblasts transduced by FGFR1OP2/wit3.0␤ lentiviral vectors (dotted lines) increased gel contraction rates. E: SNP1, SNP2, and SNP1/2 of FGFR1OP2/wit3.0␤ increased collagen gel contraction rates.…”
Section: Discussionmentioning
confidence: 99%
“…52 Cocultured fibroblast would not cause any concern in terms of overproliferation since it was shown that fibroblasts in floating collagen matrices have low levels of DNA synthesis and become quiescent. [53][54][55] Thus, bystander fibroblasts will not have any negative impact on islet viability and function.…”
Section: Discussionmentioning
confidence: 99%
“…Cells interacting with collagen matrices exhibit distinct patterns of signaling and migration [18][19][20][21] and remodel matrices both locally and globally [5,6,[22][23][24]] to achieve tensional homeostasis [25,26]. While cells on planar surfaces can modulate their cytoskeletal function in response to surface mechanics [27,28], they have little capacity to modulate the overall molecular organization and mechanical properties of the ECM-coated planar surface itself.…”
Section: The Four Quadrants Of Cell Mechanicsmentioning
confidence: 99%